2020
DOI: 10.1177/0361198120930225
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Face and Content Validity of a Survey to Assess Users’ Perceptions of Automated Vehicles

Abstract: Fully automated vehicles hold promise for providing numerous societal benefits, including drastically reducing road fatalities. However, we know little about the adoption practices of individuals related to automated vehicles. To assess transportation users’ perceptions of automated vehicles, a 40-item survey was designed using guidance from several technology acceptance models. A focus group was used to assess face validity to ensure the items appeared credible and understandable to the layperson. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 52 publications
3
39
0
Order By: Relevance
“…The Autonomous Vehicle User Perception Survey [AVUPS; ( 36 , 38 )] contains three subscales (i.e., intention to use, perceived barriers , and well-being ) and a total acceptance score. The AVUPS showed acceptable face validity and the mean content validity index was 96% ( 38 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Autonomous Vehicle User Perception Survey [AVUPS; ( 36 , 38 )] contains three subscales (i.e., intention to use, perceived barriers , and well-being ) and a total acceptance score. The AVUPS showed acceptable face validity and the mean content validity index was 96% ( 38 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…During initial scale development ( Mason et al, 2020 ), nine AVUPS items were negatively worded and EFA results indicated one item did not scale, one item loaded on IU (Factor 1), and seven items loaded on barriers (Factor 2). The items were developed to avoid response biases associated with multi-item scales that are worded in a single direction (i.e., acquiescence) as suggested by several psychometricians ( Churchill, 1979 ; Baumgartner and Steenkamp, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…The approach adopted in this study and the initial survey development ( Mason et al, 2020 ) ensured that the survey instrument design included items that were relevant, concise, and clear. Specifically, the conceptual model guided item generation from the extant literature, followed by an assessment to determine face validity, and two rounds of reviews from subject-matter experts to establish content validity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations